2002
DOI: 10.21273/hortsci.37.5.759
|View full text |Cite
|
Sign up to set email alerts
|

Improving Cut Flower Production of Balloon Flower

Abstract: Experiments aiming to adapt the perennial balloon flower (Platycodon grandiflorus) as a commercial cut flower crop were conducted for 4 years under various growing conditions: four controlled-temperature rooms at two photoperiods in a phytotron, heated and unheated greenhouses, and a saran net-house (15% shade). Best flower yield was obtained following crown cooling for 12 weeks at 2 to 4 °C. Platycodon is a day-neutral plant, but produce more flowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…hadecloth is used in the production of a variety of vegetable, fruit, and ornamental crops, especially in tropical and subtropical regions (Armitage, 1991;D ıaz-P erez, 2013;Halevy et al, 2002;Ili c et al, 2012;Marini and Sowers, 1990;Wolff and Coltman, 1990). Shadecloth provides a microclimate with reduced PAR, air temperature, root zone temperature, and changes in relative humidity (Kittas et al, 2012;Stamps, 2009).…”
mentioning
confidence: 99%
“…hadecloth is used in the production of a variety of vegetable, fruit, and ornamental crops, especially in tropical and subtropical regions (Armitage, 1991;D ıaz-P erez, 2013;Halevy et al, 2002;Ili c et al, 2012;Marini and Sowers, 1990;Wolff and Coltman, 1990). Shadecloth provides a microclimate with reduced PAR, air temperature, root zone temperature, and changes in relative humidity (Kittas et al, 2012;Stamps, 2009).…”
mentioning
confidence: 99%
“…In P . grandiflorus , flowering is accelerated at elevated temperatures, whereas the treatment of GA 3 does not affect flowering [ 18 , 43 ], indicating the importance of ambient temperature to P . grandiflorus flowering.…”
Section: Resultsmentioning
confidence: 99%
“…It was shown that the flowering timing of P . grandiflorus was not affected by photoperiod and gibberellin together but was significantly accelerated by high temperature [ 18 ]. Similarly, the day-natural tomato flowering is regulated by the FT-homologue SFT/SP3D gene, which is regulated independently of CO and day length [ 11 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Its root, called doraji in Korea, jiegeng in China, and kikyo in Japan, has been widely used as a traditional medicine in these countries [ 2 ]. In addition, P. grandiflorus , which is also used as a vegetable and an ornamental plant, shows strong ecological adaptability facilitated by resistance to drought, cold, and disease [ 3 , 4 ]. Codonopsis lanceolata (bonnet bellflower) exhibits various health benefits including antioxidant, antimicrobial, anti-inflammatory, and immune-modulating properties.…”
Section: Introductionmentioning
confidence: 99%